Review of the genus Miloderes Casey, 1888 (Coleoptera: Curculionidae: Entiminae), with desciptions of three new species - Dam, Matthew H. Van; O’brien, Charles W. (Zootaxa, 2015)
The genus Miloderes Casey, 1888 is reviewed and three new species are described. The genus now has eight valid species: M. amargosensis sp. nov., M. mercuryensis Tanner, M. nelsoni Kissinger, M. panamintensis sp. nov., M. setosus Casey, M. tingi Tanner, M. ubehebensis sp. nov. and M. viridis Pierce. Miloderes allredi Tanner, 1974 is a new junior synonym of M. viridis Pierce, 1910. The relationships of the species are discussed based on morphological characters from external morphology as well as from the endophallus. A key to species is provided.